2012
DOI: 10.1055/s-0032-1317018
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Oxidative Dimerization of Alcohols to Esters

Abstract: 2,2,6,6-Tetramethylpiperidine-1-oxyl (TEMPO) catalyzes the direct oxidation of primary alkyl alcohols to symmetric esters at 1-2 mol% loadings. These rapid reactions take place at room temperature to afford the products in yields of 55-99%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The diol A1 was obtained from a ring-opening reaction of cyclohexene oxide with propylene glycol, which was next treated with trichloroisocyanuric acid (TCCA) and 2,4,6-collidine in presence of (2,2,6,6-Tetramethylpiperidin-1-yl)oxyl (TEMPO) as a catalyst to yield M1 at 37% overall yield on the gram scale. 78 The hydroxyl acid A2 was obtained by using 3-mercaptopropionic acid as a nucleophile. Lactonization of A2 afforded monomer M2 in 56% overall yield for two steps on a 10 g scale.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The diol A1 was obtained from a ring-opening reaction of cyclohexene oxide with propylene glycol, which was next treated with trichloroisocyanuric acid (TCCA) and 2,4,6-collidine in presence of (2,2,6,6-Tetramethylpiperidin-1-yl)oxyl (TEMPO) as a catalyst to yield M1 at 37% overall yield on the gram scale. 78 The hydroxyl acid A2 was obtained by using 3-mercaptopropionic acid as a nucleophile. Lactonization of A2 afforded monomer M2 in 56% overall yield for two steps on a 10 g scale.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the basis of the control experiments and according to that reported for similar cases, 1821 the probable reaction pathway is put forward, as shown in Scheme 4. First, TCCA reacts with TEMPO to form N -oxoammonium ion I , which oxidizes the primary alcohol through intermediate II to the corresponding aldehyde IV , giving hydroxylamine III .…”
Section: Resultsmentioning
confidence: 97%
“…TCCA is a commercially available and very cheap oxidant. 1517 The combination of TEMPO and TCCA has been used catalytically and stoichiometrically for the oxidation of primary alcohols to aldehydes, 18 α-chloroaldehydes, 19 carboxylic acids, 20 esters, 21 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…For our studies we chose trichloroisocyanuric acid (TCCA) as terminal oxidant for TEMPO-catalyzed oxidative esterification of alcohols because it is a very cheap and non-toxic reagent and has been used with success in a number of TEMPO-catalyzed oxidation reactions. 17,20 After some experimentation on the model substrate 1f, the HFIP ester 2f could be obtained in 82% yield by treatment of the alcohol 1f in CH 2 Cl 2 21 with TEMPO (5 mol%) and TCCA (1.2 equiv) added by portions at 0 °C followed, after consumption of the alcohol, by HFIP alcohol (2 equiv) and pyridine (4 equiv) and stirring the suspension for 30 minutes at room temperature (Table 1, entry 6). The resulting ester was easily purified by filtration of the suspension through a pad of silica gel.…”
Section: Syn Lettmentioning
confidence: 99%
“…15,16 Later on, Szpilman and co-workers showed that this oxidation could work as well by using a catalytic amount of TEMPO and a terminal oxidant. 17 They also reported a new method of mixed anhydride synthesis from aldehydes and pivalic acid with a TEMPO/t-BuOCl/ pyridine system and these mixed anhydrides were further transformed to esters and amides via a one-pot procedure. 18 In 2013, Leadbeater and co-workers reported the oxidative esterification of aldehydes to HFIP esters using the Bobbitt oxidation procedure.…”
Section: -98% 53-93%mentioning
confidence: 99%